2016
DOI: 10.1038/ncomms10426
|View full text |Cite
|
Sign up to set email alerts
|

Misorientation-angle-dependent electrical transport across molybdenum disulfide grain boundaries

Abstract: Grain boundaries in monolayer transition metal dichalcogenides have unique atomic defect structures and band dispersion relations that depend on the inter-domain misorientation angle. Here, we explore misorientation angle-dependent electrical transport at grain boundaries in monolayer MoS2 by correlating the atomic defect structures of measured devices analysed with transmission electron microscopy and first-principles calculations. Transmission electron microscopy indicates that grain boundaries are primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
172
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(188 citation statements)
references
References 28 publications
15
172
1
Order By: Relevance
“…The monolayer MoS 2 samples were grown on sapphire using chemical vapour deposition20, and then transferred to TEM grids using the polymethyl methacrylate (PMMA) method as a free-standing sheet21. Excellent quality of the as-grown MoS 2 crystal was confirmed by TEM (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The monolayer MoS 2 samples were grown on sapphire using chemical vapour deposition20, and then transferred to TEM grids using the polymethyl methacrylate (PMMA) method as a free-standing sheet21. Excellent quality of the as-grown MoS 2 crystal was confirmed by TEM (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the hexagonal atomic structure of semiconducting MoS 2 in the 2H phase, the misorientation angle ranges from 0°to 60°3 3,36 . The atomic defect structures in MoS 2 grains and GBs greatly affect the mechanical, electrical, and optoelectronic properties of MoS 2 -based devices 35,[37][38][39][40][41][42][43] . To thoroughly explore the degradation behaviors of MoS 2 grains and GBs with different inter-grain misorientation angles, we selected four samples with different angles and characterized their original morphologies and structures.…”
Section: Resultsmentioning
confidence: 99%
“…1g) 33 . Notably, the shape of GBs depends on the relative growth rates of the two adjacent edges, which are not easily distinguished in SHG images when the misorientation angle approaches 0°or 60°because of the 60°p eriodicity caused by the six-fold rotational symmetry of the MoS 2 lattice [33][34][35] . As demonstrated later, such a simple method of confirming the GBs enables the analysis of degradation processes.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the CVD deposition of MoS 2 on a commonly used SiO 2 /Si substrate typically results in the formation of a 2D polycrystalline material, composed by several domains with a triangular shape separated by GBs [77]. The structural and electrical properties of GBs have been the object of many experimental and theoretical investigations in the last years [78,79], due to their impact on the mobility of MoS 2 field effect transistors and their role in peculiar extrinsic charge transport phenomena in MoS 2 [80,81]. Recent investigations indicated that inter-domains scattering (due to GBs) can play a major role (as compared to the intra-domain scattering due to localized defects [68,82,83]) in the degradation of the MoS 2 mobility, especially for certain misorientation angles between MoS 2 domains [81].…”
Section: Local Resistance Mapping At Grain Boundaries In Cvd Grown Mosmentioning
confidence: 99%
“…The structural and electrical properties of GBs have been the object of many experimental and theoretical investigations in the last years [78,79], due to their impact on the mobility of MoS 2 field effect transistors and their role in peculiar extrinsic charge transport phenomena in MoS 2 [80,81]. Recent investigations indicated that inter-domains scattering (due to GBs) can play a major role (as compared to the intra-domain scattering due to localized defects [68,82,83]) in the degradation of the MoS 2 mobility, especially for certain misorientation angles between MoS 2 domains [81]. To this purpose, complex transistors structures and modeling for electrical data interpretation have been employed to evaluate the impact of the specific GB configurations on the MoS 2 channel mobility [81].…”
Section: Local Resistance Mapping At Grain Boundaries In Cvd Grown Mosmentioning
confidence: 99%